2003
DOI: 10.1128/aem.69.4.1936-1943.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and Characterization of Acidophilic Microorganisms Isolated from a Pilot Plant Stirred-Tank Bioleaching Operation

Abstract: Microorganisms were enumerated and isolated on selective solid media from a pilot-scale stirred-tank bioleaching operation in which a polymetallic sulfide concentrate was subjected to biologically accelerated oxidation at 45°C. Four distinct prokaryotes were isolated: three bacteria (an Acidithiobacillus caldus-like organism, a thermophilic Leptospirillum sp., and a Sulfobacillus sp.) and one archaeon (a Ferroplasma-like isolate). The relative numbers of these prokaryotes changed in the three reactors sampled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
144
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 282 publications
(153 citation statements)
references
References 28 publications
5
144
2
2
Order By: Relevance
“…thermosulfidooxidans were among the most common species found in stirred tank processes in mesophilic conditions (Olson et al 2003;Dopson and Lindström 2004;Shippers 2007). The reduced number of detected strains demonstrated once more the limited diversity of consortia that thrive in bioleaching processes (Okibe et al 2003). At.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…thermosulfidooxidans were among the most common species found in stirred tank processes in mesophilic conditions (Olson et al 2003;Dopson and Lindström 2004;Shippers 2007). The reduced number of detected strains demonstrated once more the limited diversity of consortia that thrive in bioleaching processes (Okibe et al 2003). At.…”
Section: Discussionmentioning
confidence: 99%
“…caldus (Okibe et al 2003;Rawlings 2005). Selection pressure being more important in continuous mode, Sulfobacillus was certainly disadvantaged by the limited availability of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, conditions (such as concentrations of soluble metals and metalloids) will vary in a continuousflow series of tanks as mineral oxidation becomes increasingly extensive, and this can have a significant impact on diversity and numbers of indigenous microbial species (e.g. Okibe et al, 2003). The homogeneity within an individual tank results in a limited ecological niche that tends often to be dominated by two to four species, although smaller numbers of other micro-organisms may be present (Table 1).…”
Section: Characteristics Of Mineral Degradation In Stirred-tank Reactorsmentioning
confidence: 99%
“…Instead of a sole species, microbial populations exhibited substantial diversity in stirred-tank, mineral-processing bioreactors and ore leaching heaps. Microbial community analysis of the leachate has shown that the microbial bioleaching communities varied in commercial mineral leaching operations, but the genus of Sulfobacillus can be detected frequently [6][7][8]. The genus Sulfobacillus was first reported by Golovacheva and Karavaiko in 1978 [9].…”
Section: Introductionmentioning
confidence: 99%